CPM411 : Photographic imaging theories and techniques / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
The course objectives are to introduce the student to the technical aspects of photography. Students will be expected to demonstrate an ability to effectively use the Digital SLR camera, mainly emphasis on manual over-ride mode, with the introduction to entry-level professional digital photography and to understand the theories of quality imaging through photography. Designing the projects or exercises, in which, allows the students a practical in problem solving, with the intention of generating plausible dynamic composition possible. Students are encouraged to be creative in the usage of art & graphic fundamentals into their composition. The students will have a comprehensive knowledge in the usage of the camera throughout from pre-visualization towards the understanding of the digital workflow